Demonstration of bidirectional photoinduced electron transfer (PET) sensing in 4-amino-1,8-naphthalimide based thiourea anion sensors - GUNNLAUGSSON, THORFINNUR; KRUGER, PAUL (My University, 2009)
The thiourea based 4-amino-1,8-naphthalimide molecules 1-5 were designed as fluorescent anion sensors and their photophysical properties investigated upon recognition of biologically relevant anions such as acetate, dihydrogen phosphate and fluoride in DMSO. Synthesised in a single step from their respective aniline precursors, 6-9, these molecules were designed on the fluorophore-spacer-receptor principle, where in the case of sensors 1-3 the thiourea anion recognition moieties were connected to the fluorophore via the 4-amino moiety, while sensors 4 and 5 had the thiourea moieties connected to the 'imide' via a CH2 spacer. The current study showed that 1-5 operated as photoinduced electron transfer (PET) sensors, as no significant changes were observed in their absorption spectra, while their fluorescence emissions were quenched upon recognition of ions such as AcO(-), H2PO4(-) and F(-), which demonstrates that bidirectional PET sensing occurs in such naphthalimide based anion sensors.
PUBLISHED
Keywords: Chemistry